Bio-Inspired Green Synthesis Of Metal Oxide Nanomaterials And Their Environmental Applications In Water Treatment. - Nayak , Saroj Kumar; Shrivastava , Shilpi (Journal of Neonatal Surgery, 2025)
Bio-inspired processing of nanomaterials has gained significant attention as a sustainable alternative to conventional chemical synthesis methods, which often involve toxic reagents and energy-intensive conditions. In this study, an eco-friendly green synthesis approach was developed for the preparation of metal oxide nanomaterials, namely zinc oxide (ZnO), copper oxide (CuO), and nickel oxide (NiO), using plant extracts and biowaste-derived bioactive compounds as natural reducing and stabilizing agents. The synthesis was carried out under ambient conditions, offering a rapid, low-cost, and environmentally benign route for nanoparticle production. Successful formation of nanomaterials was confirmed through UV–Visible spectroscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and Fourier-transform infrared spectroscopy (FTIR). UV–Visible spectra revealed characteristic absorption peaks corresponding to nanoscale metal oxides, while XRD analysis confirmed high crystallinity with average crystallite sizes ranging from 22 to 32 nm. Morphological studies indicated predominantly spherical to quasi-spherical nanoparticles with uniform distribution and minimal agglomeration. FTIR analysis confirmed the presence of phytochemical functional groups responsible for nanoparticle stabilization. The green-synthesized nanomaterials exhibited excellent environmental performance, achieving up to 93% photocatalytic dye degradation, 94% heavy metal removal efficiency, and strong antibacterial activity against waterborne pathogens. Reusability studies demonstrated stable performance over multiple cycles, and toxicity assessment indicated low hemolysis values below 5%. Overall, the results demonstrate that bio-inspired nanomaterials synthesized via green routes are efficient, safe, and scalable candidates for sustainable water treatment applications.